Assessing the awareness and perception of waqf among business owners in Gombe State, Nigeria - Musa Abdu; Abdullahi Abubakar Lamido; Adamu Jibir (Islamic Economic Studies (IES), 2023)
Purpose - The literature about the dynamics of Muslims' awareness and perception of waqf has been generally scarce,especially in Nigeria. As renewed efforts are emerging to develop a new waqf regime in the country, this study examines this aspect in Gombe metropolis, Nigeria, with a view to identifying the key factors shaping people's perception and awareness towards waqf. Design/methodology/approach - To achieve the objective of this study, primary data were collected through a survey among 494 business owners in the Gombe metropolis. The data were then analysed using probit and Tobit regression models. Findings - The study found that altruistic behaviour, religiosity level, educational level and young age are among the factors that determine people's perception and awareness towards donating to waqf among business owners in Gombe. Altruism and young age embolden businesspersons to recognise the effectiveness of waqf institutions in solving socioeconomic challenges. Practical implications - The findings of this study imply that waqf has huge potential in the study area and that with well-structured, organized waqf education programmes within the business community using diverse avenues, a robust waqf sector can be developed. Originality/value - As far as the study area and the entire Nigerian Islamic economics and finance landscape is concerned, the study has explored a novel research area. Given the infant stage of empirical studies on waqf in Nigeria, there are virtually no previous attempts to examine the awareness and perception of businesspersons towards waqf; variables that are key to the development of an effective sector.
Keywords: D10; D11; Z12; 330; Awareness; Businesspersons; Logit; Nigeria; Perception; Probit; Waqf